2004
DOI: 10.1002/ar.a.20131
|View full text |Cite
|
Sign up to set email alerts
|

Differential expression of estrogen receptors (ERα/ERβ) in testis of mature and immature pigs

Abstract: High affinity estrogen receptors (ERs) mediate estrogen action in male reproductive tissues. The objective of the present study was the immunolocalization of estrogen receptor ␣ and estrogen receptor ␤ in immature and mature testes of pig, a species in which the role of estrogens on gonadal function is scarcely known. Testes from 3 and 18 month-old pigs were investigated. Immunohistochemistry was performed on paraffin embeddedtissues using both mouse anti-human monoclonal IgG ER␣ and IgG ER␤ 1 isoform. Western… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 41 publications
2
23
1
Order By: Relevance
“…In SM satellite cell myoblasts the staining was even restricted to the cytoplasm. Our results are consistent with the Wndings of Carpino et al (2004) and Rago et al (2004), who detected immunoreactivity of MCA-1974ST exclusively as nuclear staining in pig epididymis and testes, respectively. With regard to the polyclonal PA1-310B, Slomczynska and Wozniak (2001) reported immunoreactivity for the porcine ovary as nuclear and/or cytoplasm staining, which was dependent on the cell type and, in oocytes, on the developmental stage.…”
Section: Figsupporting
confidence: 95%
See 2 more Smart Citations
“…In SM satellite cell myoblasts the staining was even restricted to the cytoplasm. Our results are consistent with the Wndings of Carpino et al (2004) and Rago et al (2004), who detected immunoreactivity of MCA-1974ST exclusively as nuclear staining in pig epididymis and testes, respectively. With regard to the polyclonal PA1-310B, Slomczynska and Wozniak (2001) reported immunoreactivity for the porcine ovary as nuclear and/or cytoplasm staining, which was dependent on the cell type and, in oocytes, on the developmental stage.…”
Section: Figsupporting
confidence: 95%
“…No immunoreactivity by Western blotting has been obtained with the MCA-1974ST antibody, which is in contrast to results reported by Rago et al (2004) for pig testis. The immunoblot with the polyclonal antibody PA1-310B revealed a positive detection of ER protein in all samples tested.…”
Section: Discussioncontrasting
confidence: 78%
See 1 more Smart Citation
“…In fact, proteins involved in estrogen biosynthesis and action, as aromatase (P450arom) and/or estrogen receptors (ERs), have been detected in developing sperm of numerous species such as rat [4-6], bank vole [7], rooster [8], boar [9,10], equine [11], brown bear [12], dog and cat [13], human [14,15]. …”
Section: Introductionmentioning
confidence: 99%
“…In addition, a recent investigation suggested that 17␤-estradiol and 5␣-androstane-3␤ (3␤-diol), a possible physiological ER␤ ligand converted from 5␣-dihydrotestosterone in the tissue, may modulate sertoli cell function through ER␤ [27]. Although expression of ER␤ in sertoli cells of the testis is evident in rats as well as mice, it remains controversial whether it is expressed in human testis [28]. ER␣ expression is regulated by multiple untranslated first exons and promoters.…”
Section: Discussionmentioning
confidence: 98%